2011
DOI: 10.1007/s00436-011-2598-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Mesocestoides spp. from intermediate hosts (rodents) in central Europe (Poland)

Abstract: Genus Mesocestoides is a representative of the small cyclophyllidean family Mesocestoididae that is found parasitizing the small intestine of carnivores. The life cycle of cestodes from this genus is complex and requires two intermediate hosts. Cysticercoids are produced in the first intermediate host (oribatid mites), which when eaten by the second intermediate host (mainly rodents, but also other mammalian species, birds, reptiles, or amphibians) form tetrathyridia in the body cavity. Because of the rich his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In a recent molecular study of tapeworms, only this Mesocestoides species was found in dogs and cats in south-east Poland [42]. A few years ago, tetrathyridia of M. litteratus were identified molecularly in M. glareolus and A. agrarius from the Wrocław area, south-west Poland [19]. Both rodent species, in which we identified M. litteratus larvae, M. glareolus and A. flavicollis, are known intermediate hosts of this species.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a recent molecular study of tapeworms, only this Mesocestoides species was found in dogs and cats in south-east Poland [42]. A few years ago, tetrathyridia of M. litteratus were identified molecularly in M. glareolus and A. agrarius from the Wrocław area, south-west Poland [19]. Both rodent species, in which we identified M. litteratus larvae, M. glareolus and A. flavicollis, are known intermediate hosts of this species.…”
Section: Discussionmentioning
confidence: 71%
“…The two most commonly reported species are M. litteratus found in red foxes (originally described as from a 'fox'), rodents, grey wolves, dogs and cats among others; and M. lineatus that has been reported from domestic/wild cats (originally described from wild cats, Felis sylvestris) and dogs, jackals and other carnivores [18]. In Poland, only one molecular study has been completed on Mesocestoides larvae from rodent hosts, and this identified M. litteratus in striped field mice Apodemus agrarius and M. glareolus from the Wrocław area (western Poland) [19]. Red foxes (Vulpes vulpes) are considered to be the principal hosts of adult Mesocestoides spp.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the commonly occurring long-tailed field mouse Apodemus sylvaticus, an important prey species of the arctic fox in Iceland (Hersteinsson 1993), is also suspected to harbor tetrathyridia of M. canislagopodis. Studies performed in other European countries have frequently confirmed Mesocestoides tetrathyridia in rodents of the genus Apodemus, for example in Poland (Zalesny and Hildebrand 2012), Bulgaria (Literák et al 2004), Sicily (Goüy de Bellocq et al 2003), Spain (Conn et al 2010), and Portugal (Eira et al 2006).…”
Section: Tetrathyridia Infectionsmentioning
confidence: 90%
“…In Europe, Yanchev (1986) reported seven Mesocestoides species; at present, 12 species are listed in the Fauna Europea database (www.faunaeur.org). Molecular tools have significantly helped to identify Mesocestoides species, both by using ordinal and generic markers such as the 28S (D1-D3), 18S, and the ITS2 of the ribosomal DNA, or more specific domains such as cytochrome c oxidase 1 (COI) and 12S of the mitochondrial DNA (Bowles and McManus 1994;Nakao et al 2000;Dinkel et al 2011;Eleni et al 2007;Hrčkova et al 2011;Littlewood et al 1999Littlewood et al , 2008Padgett et al 2013;Waeschenbach et al 2007;Jabbar et al 2012;Zalesny and Hildebrand 2012). Unfortunately, the use of these new tools has also led to submission of haplotypes without proper morphological characters for identifications (Foronda et al 2007;Padgett et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Mesocestoides sp. requires an unknown first intermediate host ( Voge, 1967 ), then small mammals or birds ( Zalesny and Hildebrand, 2012 ) as second intermediate hosts, respectively, with rodents being a likely source of infection for hunting dogs ( Krucken et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%